The Effect of Medroxy Progesterone Acetate Hormone Administration to Endometrial Thickness of the Female Rattus norvegicus Wistar strain - Devi Yulita (Faculty of Medicine, Universitas Andalas, 2020)
Many alternative contraceptives can be used as needed. The most effective type of contraception is injection contraception because it is relatively safe, effective, simple and inexpensive. Contraceptive users must be selective in choosing contraception because there is no method of contraception that is safe and effective for all acceptors. The side effects of Medroxy Progesterone Acetat injection include bleeding disorders such as amenorrhoea, weight gain, high blood pressure, acne, spotting. Medroxy Progesterone Acetat is a progestin contraceptive regimen that is often used and works long-term. The mechanism of action of Medroxy Progesterone Acetate injection is to inhibit gonadotropin secretion so that it will prevent the maturation of primary follicles in the ovary and also prevent ovulation and cause endometrial depletion. The research design is the post test only control group design. The population in this research  are the white rats species Rattus norvegicus Wistar strain. The samples are taken randomly from all populations that met the following sample criteria: Female rats, Aged 12-14 weeks, having a body weight of 150 - 200 grams. The results showed that Medroxy Progesterone Acetate hormone affects the thickness of the endometrium, and there is a difference in the histological picture of endometrial thickness due to the administration of the Medroxy Progesterone Acetate hormone and without the administration of the Medroxy Progesterone Acetate hormone